Mechanisms Mediating the Synergistic Anticancer Effects of Combined γ-Tocotrienol and Sesamin Treatment - Akl, Mohamed R.; Ayoub, Nehad M.; Sylvester, Paul W. (Planta Medica, 2012)
Epidemiological studies have highlighted the ability of phytochemicals to reduce the risk of breast cancer by attenuating specific intracellular signaling pathways that regulate cell proliferation and survival. γ-Tocotrienol is a natural form of vitamin E that displays potent anticancer activity at doses that have no discernible toxicity toward normal cells. Sesamin is an abundant phytochemical found in sesame seed oil that also shows antiproliferative and antiangiogenic activity against human breast cancer cells. In this study, the combined treatment of subeffective doses of γ-tocotrienol and sesamin caused a synergistic inhibition of murine +SA mammary epithelial cell growth, as determined by the MTT assay and immunofluorescent Ki-67 staining. Western blot studies revealed that combined low-dose treatment of γ-tocotrienol and sesamin caused a marked reduction in EGF-induced ErbB3 and ErbB4 receptors phosphorylation (activation) and a relatively large decrease in intracellular levels of total and/or phosphorylated c-Raf, MEK1/2, ERK1/2, PI3K, PDK1, Akt, p-NFκB, Jak1, Jak2, and Stat1, as compared to cells treated with only one compound or in the vehicle-treated control group. These findings demonstrate that the synergistic growth inhibitory effects of γ-tocotrienol and sesamin treatment are associated with suppression of EGF-dependent mitogenic signaling in mammary tumor cells and suggest that dietary supplementation with these phytochemicals may provide some benefits in the prevention and/or treatment of breast cancer.
Keywords: γ-tocotrienol; sesamin; ErbB receptors; phytochemicals; breast cancer